2023
DOI: 10.1002/app.53688
|View full text |Cite
|
Sign up to set email alerts
|

Study on preparation and performance of advanced nano‐modified epoxy asphalt

Abstract: The rapid growth in traffic volume and loads has increased the demand for high strength and durability paving materials. As the primary paving material of long-life pavements and long-span steel bridge decks, epoxy asphalt (EA) has the problems of poor tensile strength and low fracture toughness. In this study, graphene oxide nanosheets (GOs) and multiwalled carbon nanotubes (CNTs) were used to improve the mechanical properties of EA. Tensile tests, segregation experiments, Fourier transform infrared analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…31 LAMs absorb the energy of ultraviolet radiation and convert it into low-energy heat, reducing the direct damage of ultraviolet energy to asphalt. 34 AOMs react with active free radicals in asphalt, stabilizing them and slowing down the chain reaction process of active free radicals in asphalt. 35 A study conducted by Hu et al 33 also indicated that the combined use of LSMs, LAMs, and AOMs can achieve the most desirable aging-resistant effects.…”
Section: Introductionmentioning
confidence: 99%
“…31 LAMs absorb the energy of ultraviolet radiation and convert it into low-energy heat, reducing the direct damage of ultraviolet energy to asphalt. 34 AOMs react with active free radicals in asphalt, stabilizing them and slowing down the chain reaction process of active free radicals in asphalt. 35 A study conducted by Hu et al 33 also indicated that the combined use of LSMs, LAMs, and AOMs can achieve the most desirable aging-resistant effects.…”
Section: Introductionmentioning
confidence: 99%